Effects of Mindfulness Training on Psychological Capital, Depression, and Procrastination of the Youth Demographic - Li LI; Mu LI (Tehran University of Medical Sciences, 2020)
Background: The incidence rate of depression in youth demographic increases year by year. High-level psychological capital is conducive to relieving depression, and mindfulness training is an effective psychotherapy. We aimed to investigate the influences of mindfulness training on psychological capital, depression, and procrastination, thereby providing a direction for psychotherapy in the youth demographic. Method: A questionnaire survey on the youths in four resident communities in the cities of Wuhan and Tai'an in China was carried out in 2020 by sending a self-rating depression scale (SDS). A total of 240 youth with SDS standard scores >53 were filtered out, as the research objects to be assessed by using SDS, positive psychological capital questionnaire (PPQ), five-facet mindfulness questionnaire (FFMQ), and pure procrastination scale (PPS). Results: Two groups showed no statistically significant differences in SDS, PPQ, FFMQ, and PPS scores before intervention. Self-efficacy, toughness, hope, optimism, and PPQ scores of the experimental group were improved significantly after intervention compared with those before the intervention, and they were significantly higher than those of the control group (P<0.05). SDS, PPQ, FFMQ, and PPS scores showed statistically significant differences before and after intervention. SDS and PPS scores of the experimental group after intervention were far lower than those of the control group, while FFMQ score was significantly higher than that of the control group (P<0.05). Conclusion: Mindfulness training can improve psychological capital of the youth demographic effectively and relieve their depression, thereby improving their procrastination.